Computer simulations of cations order‐disorder in 2:1 dioctahedral phyllosilicates using cation‐exchange potentials and monte carlo methods. Issue 19 (24th May 2014) - Palin, Erika J.; Dove, Martin T.; Redfern, Simon A. T.; Ortega‐Castro, Joaquín; Sainz‐Díaz, Claro Ignacio; Hernández‐Laguna, Alfonso; Hernández‐Laguna, Alfonso; Sainz‐Díaz, Claro Ignacio
<x xml:space="preserve">Abstract</x> This article reviews the use of Monte Carlo methods with cation‐exchange potentials and effective Hamiltonians, based on empirical potentials and quantum‐mechanical calculations, for the study of cation ordering in phyllosilicates. The basic methodology is described, and the application of the methods is illustrated with a number of key example case studies. These include Al–Si ordering in muscovite, Al–Fe–Mg ordering (both binary and ternary compositions) in the octahedral illite/smectite sheet, examination of the ordering behavior of phengite, in which the octahedral sites are occupied by Al and Mg and the tetrahedral sites by Al and Si, and Al–Si ordering in the tetrahedral phyllosilicate sheet with variable Al:Si ratio. In several cases, complex ordering processes were found. The essential conclusion from this work is that computer simulation studies of this nature can be a valuable tool in ordering studies of many nanomaterials. © 2014 Wiley Periodicals, Inc.